Personality Traits, Migration Intentions, and Cultural Distance - Didier Fouarge; Merve Nezihe Özer; Philipp K. Seegers (Institute of Labor Economics (IZA), 2019)
This paper investigates the relationship between Big Five personality traits and individuals' intentions to migrate in countries that vary in their culture. Using data collected from university students in Germany, we find that extraversion and openness are positively associated with migration intentions, while agreeableness, conscientiousness, and emotional stability negatively relate to migration intentions. Openness positively and extraversion negatively relate to the willingness to move to culturally distant countries after controlling for geographic distance and economic differences between countries. Using language as a cultural distance indicator provides evidence that extravert and conscientious individuals are less likely to prefer linguistically distant countries while agreeable individuals tend to consider such countries as potential destinations.
Keywords: D91; J61; Z1; 330; migration intentions; destination choice; cultural distance; Big Five personality traits